Differences in Ethical Perceptions of Tax Avoidance between Lecturers and University Students - Rahadian Cahyadi; Melsa Jumliana; Fika Hartina Sari; Nur Asmi Ainun Kamal; Sitti Jam'iah; Sri Rahayu Indah Azhari (Jurnal Ekonomi Balance, 2026)
Tax avoidance is legally distinct from tax evasion, yet aggressive avoidance remains ethically contested because formal compliance may conflict with fairness, public responsibility, and the intended purpose of tax rules. This study synthesizes recent evidence on differences in ethical perceptions of tax avoidance between university lecturers and students and identifies the mechanisms that may explain any group difference. A structured literature review was conducted on 18 peer-reviewed journal articles published from 2021 to 2026. Studies were screened and coded by population, research design, tax knowledge, professional experience, perceived fairness, institutional trust, fiscal morale, ethics education, moral obligation, and individual ethical orientation. The synthesis finds that direct matched evidence comparing lecturers and students is still insufficient; academic status alone cannot be treated as a causal determinant of ethical judgment. More consistent evidence shows that applied tax knowledge, professional exposure, fairness and trust, fiscal morale, and moral obligation shape tax-related ethical evaluations. Student-focused studies also indicate that ethics education and experiential learning can strengthen moral reasoning, although effects depend on tax comprehension and ethical mindset. Substantial within-group variation, including differences associated with Machiavellian orientation, further limits categorical conclusions. The study therefore proposes a conditional role-experience framework and recommends matched lecturer-student research using identical tax-planning scenarios. For higher education, the findings support case-based tax ethics instruction that integrates technical competence with fairness, institutional responsibility, and the social consequences of aggressive avoidance.